(untitled) (Research, Society and Development, 2022)
The objective was to identify whether continuing education in health is applied as a qualification strategy for workers belonging to the context of the Regulatory Centers and to analyze the impact of the applicability of this strategy to guarantee access to health services by users. This is an integrative literature review carried out through the Virtual Health Library portal, in the following databases: Latin American and Caribbean Literature on Health Sciences, Nursing Database and Coleciona SUS; in addition to the Capes periodicals portal through the following databases: Scientific Eletronic Library Online, SciVerse Scopus and the PubMed Database of the U.S. National Library of Medicine, considering a 5-year time frame. Eleven publications were selected, establishing two categories, namely: professional practices and team qualification; and organization of work processes. Professional practices should start from an interdisciplinary construction, exploring the problems arising from the work environment, in articulation with the entire Health Care Network, with a sense of co-responsibility. The (re)organization of the work processes through educational interventions constitutes a successful strategy in the transformation of more effective and permanent practices, with the engagement of all the actors. By developing strategies based on continuing education, management, professionals and especially the population can articulate together and based on the local reality, environments for exchange, dialogue and recognition of the labor practice, guided by a reflective and participatory link, resulting in improved quality and therefore in guaranteed access to health care.